Fast Fashion, Fashion Brands and Sustainable Consumption - Muthu, Subramanian Senthilkannan (Textile Science and Clothing Technology, 2019)
This book discusses the connection between fast fashion brands and customer-centric sustainability. It highlights what consumers can do with fast fashion and the important aspects that need to be addressed to make fast fashion sustainable. Fast fashion is an inevitable element in today's fashion business cycle and its adverse impacts on sustainable fashion are a major issue.